Analysis of Microteaching Learning - Riki Suliana; Cicik Pramesti; Suryanti Suryanti; Ayu Silvi Lisvian Sari (Journal of Education and Learning Mathematics Research (JELMaR), 2022)
The basic skills of teaching students who are prospective teachers of Mathematics Education are needed to improve the competence of prospective teachers when entering the world of education. This study aims to determine the process of teaching and learning activities and basic teaching skills of prospective students of Mathematics Education teachers in microteaching at UNIPA Campus Blitar. This type of research includes descriptive research with a qualitative approach. The research subjects were 6 students. There are two techniques used in this study, namely observation techniques with open and closed answers. The activities of students of the Mathematics Education Study Program at UNIPA Campus Blitar regarding the Implementation of Microteaching in the teaching skills of prospective teacher students in the 5 main components of Basic Teaching skills have a total average of 76.1%, which is included in the good category.